Kualitas Produk Persepsi Harga dan Electronic Word of Mouth Meningkatkan Keputusan Pembelian melalui Brand Image - Amallia Rahmah Sari; Parlagutan Silitonga (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the effect of product quality, price perception, and electronic word of mouth (EWOM) on purchase decisions with Brand Image as a mediating variable at Tomoro Coffee. This research uses a quantitative approach with data collection through questionnaires to 250 respondents who are visitors to Tomoro Coffee with Accidental Sampling technique. Data analysis was carried out using the PLS-SEM method with the help of SmartPLS 3.0 software. The results showed that product quality, price perception, and EWOM have a positive and significant effect on Brand Image, and have a direct effect on purchase decisions. However, Brand Image does not have a significant effect on purchase decisions, so it does not mediate the relationship between the three independent variables and purchase decisions. These results indicate that purchase decisions are more directly influenced by product quality, price perceptions, and EWOM. These findings provide important implications for marketing strategies by focusing more on product quality, competitive prices, and utilizing EWOM to improve consumer purchase decisions.